2021
DOI: 10.3390/jcm10081647
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Therapy-Related Cardiovascular Complications in Clinical Practice: Current Perspectives

Abstract: Cardiovascular (CV) diseases and cancer are the leading causes of death in Europe and the United States. Both diseases have extensive overlap and share common risk factors, symptoms, and outcomes. As the number of patients with both cancer and CV diseases continues to rise, the field of cardio-oncology is gaining increased attention. A frequent problem during anti-cancer treatment is cardiotoxicity caused by the side-effects of chemo-, immuno-, targeted, and radiation therapies. This problem may manifest as ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 114 publications
0
16
0
2
Order By: Relevance
“…По некоторым данным распространенность преходящих изменений на ЭКГ по типу ишемических достигает 68%, а в сочетании с повышением маркеров повреждения миокарда -43%. Летальность от кардиальных осложнений 5-ФУ составляет от 2,2 до 13% [138,141,135,139,136].…”
Section: патофизиология и клинические проявления ибс связанной с прот...unclassified
See 1 more Smart Citation
“…По некоторым данным распространенность преходящих изменений на ЭКГ по типу ишемических достигает 68%, а в сочетании с повышением маркеров повреждения миокарда -43%. Летальность от кардиальных осложнений 5-ФУ составляет от 2,2 до 13% [138,141,135,139,136].…”
Section: патофизиология и клинические проявления ибс связанной с прот...unclassified
“…До начала терапии с потенциальной сосудистой токсичностью следует определить риск развития ИБС. К факторам риска ишемических осложнений относятся [137,134,139] Низкий риск -отсутствие ФР или наличие одного среднего ФР -1 балл (Low risk = no risk factor OR one medium1 risk factor); Средний риск -наличие средних ФР в сумме 2-4 балла (Medium risk = medium risk factors with a total of 2-4 points);…”
Section: диагностика ибс ассоциированной с противоопухолевой терапией...unclassified
“…The primary phenolic compounds in the three plant extracts employed to study liver detoxification treatment dandelion-leaf and root extracts, as well as a commercial root powder-were identified by HPLC analysis 9 . Oil Red O staining and triglyceride levels study both revealed lower lipid and triglyceride buildup.…”
Section: Herbal Detox Agents For Livermentioning
confidence: 99%
“…Increased radiation-related cardiotoxicity has been observed in some patients with solid tumors during long-term follow-up, with an incubation period of more than 10 years ( 3 , 4 ). This increased risk of CVD begins within the first 5 years after radiotherapy and increases over time, lasting more than 20 years ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%